Sistem Informasi Manajemen Karyawan Pada PT. Mitra Beton Mandiri - Zarnelly Zarnelly; Istanti Dwi Fajarrini (UIN Sultan Syarif Kasim Riau, 2015)
PT. Beton Mitra Mandiri has eight factories and 125 employees. The HRD difficulties in managing employee data in terms of attendance reporting, recording loan funds, and record employee leave, resulting in frequent delays that resulted in delays in the calculation absent employee's salary, cheating number of employees on leave, and the buildup of files as well as the impact on the decline in the productivity of company so it cannot meet the project targets. To overcome the above problems built an Employee Management Information System using Method Framework for the Application of Systems Thinking (FAST). There are five steps that used FAST Scope Definition Phase, Problem Analysis Phase, Analysis Requirements Phase, Logical Design Phase, and Phase Decision Analysis. A result from this study is Management Information System Web-based Employee has been implemented. Black box testing results presentation system with success was 96.8% and the test 94.4% user acceptance testing.Keywords: Human Resource Development, Framework FAST Method, PT. Mitra Beton Mandiri, Management of Information System of Employe